Stakeholder Management of Jakarta’s Light Rail Transit Using Stakeholder Analysis - Khrisna Yudi; Ayomi Dita Rarasati; Achmad Jaka Santos Adiwijaya (Diponegoro University, 2017)
Stakeholders involvement in infrastructure development c.q. Light Rail Transit (LRT) has a significant role since they affect the success of infrastructure management. This paper is primarily aimed to identify key stakeholders and responses that need to be applied to them. On the initial stage, a list of stakeholders was developed using research strategies such as case study and literature review. Sources were then chosen with certain criteria. They were assigned to score each stakeholder on the list. A stakeholder analysis was conducted to obtain a list of key stakeholders that have a significant impact on Jakarta’s LRT.